2021
DOI: 10.1007/s11596-021-2501-4
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence to Diagnose Tibial Plateau Fractures: An Intelligent Assistant for Orthopedic Physicians

Abstract: Objective To explore a new artificial intelligence (AI)-aided method to assist the clinical diagnosis of tibial plateau fractures (TPFs) and further measure its validity and feasibility. Methods A total of 542 X-rays of TPFs were collected as a reference database. An AI algorithm (RetinaNet) was trained to analyze and detect TPF on the X-rays. The ability of the AI algorithm was determined by indexes such as detection accuracy and time taken for analysis. The algorithm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Others have indicated opportunities for AI to leverage big data to obtain insights and develop strategies for managing specific diseases, including opioid use disorders [1]. Another example of recognition and interpretation was offered by Liu et al [10], in which AI and orthopaedic surgeons correctly identified a similar number of tibial plateau fractures (accuracy 0.91 versus 0.92). These use cases could improve efficiency and accuracy in diagnosis and treatment, ultimately leading to better patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Others have indicated opportunities for AI to leverage big data to obtain insights and develop strategies for managing specific diseases, including opioid use disorders [1]. Another example of recognition and interpretation was offered by Liu et al [10], in which AI and orthopaedic surgeons correctly identified a similar number of tibial plateau fractures (accuracy 0.91 versus 0.92). These use cases could improve efficiency and accuracy in diagnosis and treatment, ultimately leading to better patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of studies with different products on fracture detection using AI on plain radiographs [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Fractures are the leading type of missed diagnosis [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…There was, however, a significant difference in the time spent assessing the X-rays, with the AI being 16-times faster than orthopedic physicians. The authors state that the working conditions for orthopedic physicians were not ideal to simulate real working conditions, since the study was conducted in nonemergency and under time-free constraints on the diagnosis process [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Liu suggests that their AI algorithm would perform even better in clinical settings. Humans have been shown to be prone to missed diagnoses when under pressure or overworked, making AI a potentially useful tool in these scenarios[ 22 ].…”
Section: Image-based Ai Applicationmentioning
confidence: 99%